2008
DOI: 10.1159/000113216
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Chronic Pain and Cognition in Cognitively Intact Older Persons and in Patients with Alzheimer’s Disease

Abstract: Background: Brain areas that are involved in cognition and mood also play a role in pain processing. Objective: The goal of the present study was to examine the relationship between chronic pain and cognition [executive functions (EF) and memory], while controlling for mood, in cognitively intact older persons and in patients with Alzheimer’s disease (AD). Methods: Two groups of subjects participated: 20 older persons without dementia and 19 patients in an early stage of probable AD who suffered from arthrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 92 publications
2
48
1
2
Order By: Relevance
“…It is worth noting that in some of the pathological conditions for which σ 1 agonists are being investigated, pain is one of the symptoms. Examples include recovery from stroke43, traumatic brain injury44 or spinal cord injury45, Alzheimer’s disease46, Parkinson’s disease47 and multiple sclerosis48. In addition, other diagnoses such as anxiety or depression often occur concomitantly to pain states49.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that in some of the pathological conditions for which σ 1 agonists are being investigated, pain is one of the symptoms. Examples include recovery from stroke43, traumatic brain injury44 or spinal cord injury45, Alzheimer’s disease46, Parkinson’s disease47 and multiple sclerosis48. In addition, other diagnoses such as anxiety or depression often occur concomitantly to pain states49.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Eccleston (1994) showed that pain affected performance on an attentional-interference task, but only when the task was at its most complex. Studies by Suhr (2003) and Scherder et al (2008), however, failed to show any executive function deficits in chronic pain patients. A study by Oosterman and colleagues (2009) actually found a positive relationship between self-reported pain and executive function (increased pain levels associated with improved cognitive function).…”
Section: Executive Functionmentioning
confidence: 95%
“…There are also studies that report no association between chronic pain and impaired cognitive function (Bell et al, 1999;Landro et al, 1997;Pincus et al, 1998;Scherder et al, 2008Suhr, 2003. Furthermore, functional deficits may manifest in the absence of measurable cognitive impairment.…”
Section: Appraisal and Caveats Of Clinical Literaturementioning
confidence: 99%
“…Extensive research has tested the common wisdom assumption that pain engages domain-general cognitive resources in non-human animals [21; 31; 32; 10; 9; 4], chronic pain patients [28; 52; 18; 68; 30; 74; 19; 51; 60], and healthy volunteers exposed to transient noxious stimuli [53; 78; 27; 1; 6; 14; 17; 57; 61; 20; 3335; 58; 64; 6971; 77; 55; 73; 2; 40; 63; 62; 12; 39; 56]. We can distinguish these studies according to the explicit hypothesis tested (Fig.…”
mentioning
confidence: 99%